Discovery and development of small-molecule inhibitors of glycogen synthase - Tang, Buyun (J Med Chem, 2020)
The over-accumulation of glycogen appears as a hallmark in various glycogen storage diseases (GSDs), including Pompe, Cori, Andersen and Lafora disease. Accumulating evidence suggests that suppression of glycogen accumulation represents a potential therapeutic approach for treating these GSDs. Using a fluorescence polarization assay designed to screen for inhibitors of the key glycogen synthetic enzyme, glycogen synthase (GS), we identified a substituted imidazole, (rac)-2-methoxy-4-(1-(2-(1-methylpyrrolidin-2-yl)ethyl)-4-phenyl-1H-imidazol-5-yl)phenol (H23), as a first-in-class inhibitor for yeast glycogen synthase 2 (yGsy2p). Data from X-ray crystallography at 2.85 Å, as well as kinetic data, revealed that H23 bound within the UDP-glucose binding pocket of yGsy2p. The high conservation of residues between human and yeast GS in direct contact with H23 informed the development of around 500 H23 analogs. These analogs produced a structure-activity relationship (SAR) profile that led to the identification of a substituted pyrazole, 4-(4-(4-hydroxyphenyl)-3-(trifluoromethyl)-1H-pyrazol-5-yl)pyrogallol, with 300-fold improved potency against human GS. These substituted pyrazoles possess a promising scaffold for drug development efforts targeting GS activity in GSDs associated with excess glycogen accumulation.